Benefícios do cicloergômetro de membros inferiores em indivíduos hospitalizados com dreno torácico: estudo de casos e uma proposta para a promoção da saúde - Brito, Suelen Guimarães de (2015)
The cycle-ergometer is an equipment that is being increasingly used because of the possibility of continuous mobilization. For this reason, it is important to conduct studies regarding the use of cycle-ergometer, because there is still no consensus about its use under certain pathological or traumatic conditions. In the hospital he is mainly used as a therapeutic resource for early mobilization of patients in intensive care unit. Hospitalized patients with pleural disease who are undergoing insertion of pleural drain, also need attention, because present risks of pulmonary and pleural compromises regarding the surgical procedure. These complications worsen the state of health of the patient, collaborate to increase mortality and hospital costs. This study aims to assess general aspects of health promotion in hospitalized patients with lung diseases from the use of a portable cycle-ergometer exercise protocol. For that the benefits obtained were verified in the tidal volume, respiratory muscle strength, functional independence and the influence on the length of stay of patients with pleural intercostal drain after a physiotherapeutic protocol using the cycle-ergometer. Is a retrospective and observational study, with description of case series and a quantitative approach. Through active search in medical records of a public hospital were selected subjects with pleural-intercostal drain that were underwent protocol using the cycle-ergometer. These patients began the exercises early in the first 24h after pleural drain insertion, and the last session was in the period up to 24h after removal of the drain, with a daily session. Were analyzed 07 patients, median age 37, being 05 patients smoking and all sedentary. According to parametric distribution or not, was used respectively the Students “t” test or Wilcoxom test. Analyzing the values obtained before starting the Protocol and the penultimate day we have the differences 63% increase in maximal inspiratory pressure ( p ≤ 0.03) , 73 % increase of the maximum expiratory pressure ( p < 0.01) , an increase of 68% of this volume ( p < 0.03) and 67% increase in the score of the functional independence measure scale ( p < 0.01), all pointing to improvement of the parameters evaluated Moreover, it has not been possible to establish the influence of the Protocol on the length of stay. It was found that the cycleergometer exercises contributed to pulmonary and functional rehabilitation of patients with pleural drain, what allows us to suggest standardizing this procedure within hospitals as an important tool for the promotion of health, since the same can enhance functional gains providing early patient autonomy. Not been found in the literature studies using the cycle Ergometer for patients with pleural drain, which supports us in considering further studies are required in the area. Keywords: exercise therapy, health promotion, physiotherapy, respiratory system.